How long does it last to systematically make bad decisions? An agent-based application for dividend policy - Victor Dragotă; Camelia Delcea (Journal of Risk and Financial Management, 2019)
Bad decisions have harmful effects on the quality of human life and an increase of their duration expands these undesirable effects. Systematic bad decisions related to dividend policy can affect the investors' quality of life in the long-term. We propose an agent-based model for the estimation of the duration of systematically making bad decisions, with an application on dividend policy. We propose an algorithm that can be used in modelling the interaction between different classes of shareholders and for predicting this duration. We perform numerical simulations based on this model using NetLogo 6.0.4. We prove that, as a result of agents' interaction, in some conditions, the duration of systematically making bad decisions can be very long: some numerical simulations suggest that, in some circumstances, this duration can significantly exceed the human lifetime. Additionally, in some conditions, the company can fail before the power is switched. This duration can increase dramatically if the shareholders have a great level of trust in the management's decisions. As an implication, a greater concern for the quality of financial education, and more performant instruments for controlling the power's decisions are required.
Keywords: 330; agent-based models; decision-making; dividend policy; investors' behavior; simulation; systematically making bad decisions